La filosofía del Derecho y el Derecho natural en los planes de estudio de las Facultades de Derecho de España (II) - Palomar Maldonado, Evaristo (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2006)
Philosophy of Law studies at Spanish universities are relatively new, especially when considering those leading to a degree in Law. This paper focuses on understanding the reason for their presence and investigates the importance of their reception and meaning of the subject of Natural Law. The core of the matter is the Science of Law, which opens the debate through some core contributions.